A new open dataset from a milling process – data for classification and estimation of tool life - Grzegorz Piecuch; Tomasz Żabiński (Scientific Data)
Abstract This data descriptor introduces a data set from a CNC machining process which includes vibration and current data recorded for 14 cutting tools used from their initial state until failure. Cuboidal samples made of 42CrMo4 material were used and milled clockwise. The research setup (Haas VF-1 and Beckhoff PAC system), experimental procedures and data were described. The data set has been made publicly available for further research and development and contains all raw and aggregated data with metadata from 968 milling cycles. Data can be used for the classification of tool condition or fault prediction, which is widely used in intelligent prediction maintenance systems.